History and Policy of Translating Poetry: Azerbaijan and Its Neighbors - Isaxanli, Hamlet (Meta, 2014)
Throughout the history of civilization the art of translation has existed as a bridge that connects different cultures. The article focuses on the history of poetic (and other) translations in the Middle East and territories abutting Azerbaijan from the Middle Ages to the 20th century. It also explores the practice of translating holy books and its influence on the region, as well as the tradition of nezire, or writing a new book under the inspiration of an original one rather than simply translating the original. The second part of the article discusses the history of poetic translation into and from the Azerbaijani language, especially translation work from Abbas Sehhet and Samad Vurghun, two renowned translators in Azerbaijani history. Finally, important aspects of the art of translating poetry are reviewed and analyzed, such as poetic forms and metaphors, rhythm and rhyme schemes, and the style of the text. The article concludes by making the point that poetry should indeed be translated; however, translators must take many factors into account in their work so that the target text reflects as much as possible the beauty of the original.